A Dataset for Three‐Dimensional Distribution of 39 Elements Including Plant Nutrients and Other Metals and Metalloids in the Soils of a Forested Headwater Catchment. Issue 6 (1st November 2017) - Wu, B.; Wiekenkamp, I.; Sun, Y.; Fisher, A. S.; Clough, R.; Gottselig, N.; Bogena, H.; Pütz, T.; Brüggemann, N.; Vereecken, H.; Bol, R.
Abstract : Quantification and evaluation of elemental distribution in forested ecosystems are key requirements to understand element fluxes and their relationship with hydrological and biogeochemical processes in the system. However, datasets supporting such a study on the catchment scale are still limited. Here we provide a dataset comprising spatially highly resolved distributions of 39 elements in soil profiles of a small forested headwater catchment in western Germany (http://teodoor.icg.kfa‐juelich.de/ibg3searchportal2/dispatch?searchparams=freetext‐Wuestebach&metadata.detail.view.id=7d37ae00‐20f6‐408e‐8660‐33bfba07c869 ) to gain a holistic picture of the state and fluxes of elements in the catchment. The elements include both plant nutrients and other metals and metalloids that were predominately derived from lithospheric or anthropogenic inputs, thereby allowing us to not only capture the nutrient status of the catchment but to also estimate the functional development of the ecosystem. Soil samples were collected at high lateral resolution (≤60 m), and element concentrations were determined vertically for four soil horizons (L/Of, Oh, A, B). From this, a three‐dimensional view of the distribution of these elements could be established with high spatial resolution on the catchment scale in a temperate natural forested ecosystem. The dataset can be combined with other datasets and studies of the TERENO (Terrestrial Environmental Observatories) Data Discovery Portal (http://teodoor.icg.kfa‐juelich.de/ibg3searchportal2/index.jsp ) to reveal elemental fluxes, establish relations between elements and other soil properties, and/or as input for modeling elemental cycling in temperate forested ecosystems. Core Ideas: A dataset of elemental concentrations for four soil horizons of a forested catchment Highly linked with a previous dataset on lateral and vertical distribution of nutrients The dataset can be used to explore biogeochemical elements and their fluxes in natural soil systems